Performance Evaluation and Optimization of Waterproof Adhesive Layer for Concrete Bridge Deck in Seasonal Frozen Region Using AHP - Weidong Jin; Yu Zhao; Wensheng Wang; Feng He (Advances in Materials Science and Engineering)
The weak connection performances between the waterproof adhesive layer, the bridge deck, and asphalt pavement are important factors that cause the bridge deck slippage and upheaval and affect the safety and durability of the bridge. In this paper, styrene-butadiene-styrene- (SBS-) modified asphalt, SBS-emulsified asphalt, rubber-modified asphalt, and AMP-100 waterproof materials are selected to study the performance of the bridge deck waterproof adhesive layer in the seasonal frozen region. The shear strength and bond strength of the four waterproof adhesive materials were obtained through the shear test and pull-out test of the composite specimens composed of four kinds of adhesive materials, diatomite rubber-particle asphalt mixture, and concrete bridge deck at different dosages and temperatures. According to the priority analysis of the factors including cost, construction difficulty, and environmental protection for the four kinds of materials by using analytic hierarchy process (AHP), SBS-modified asphalt is obtained as the most suitable waterproof adhesive layer of diatomite rubber particle asphalt mixture bridge deck in seasonal frozen region.